Home-based crisis team in North Cork service description and patient-related outcomes. (14th December 2017) - Lalevic, G.; Suhail, A.; Doyle, H.
Abstract : Objective: Home-based crisis team (HBCT) in North Cork was established in 2013 to provide short term, intensive home treatment to people who are experiencing acute mental health problems, with the aim of averting hospital admission wherever possible or supporting patients discharged from hospital. Methods: A retrospective descriptive study design was adopted to describe the activities of the North Cork HBCT over a 1 year period. Data were analysed using R version 3.4.0 for Windows. Results: A total of 388 patients were referred to the HBCT in 2015, of which 328 required assessments. General practitioners (GPs) made 56% of all referrals. The most common referral reason was low mood (40%). Stepped-up care to the psychiatric inpatient unit was required for 12.4% of patients, 62% were discharged to the outpatient clinic for routine follow-up. Conclusion: Many common psychiatric presentations can be managed at home with the support of the HBCT although hospital admission is required for significant numbers.